Correlation of C-Reactive Protein and Blood Culture in Neonatal Sepsis - Niza Monga; Nitya Vyas; Babita Sharma (JCDR Research and Publications Pvt. Ltd., 2018)
Introduction: In neonates, septicaemia is one of leading cause of morbidity and mortality. Therefore, timely diagnosis is important to prevent fatal outcome. C-reactive protein is an important biomarker that aids in the timely diagnosis of neonatal septicaemia. Aim: The present study was carried out to determine the accuracy of CRP in the diagnosis of neonatal septicaemia and to compare it with blood culture. Materials and Methods: One hundred neonates suspected of neonatal sepsis were included in the study over a period of one year. Blood culture and qualitative assessment of CRP was done for all the patients. CRP quantification was done for the patients who were CRP positive. Results: Of the 100 neonates studied, 47 were blood culture positive while 70 were CRP positive. The sensitivity, specificity, positive and negative predictive values and diagnostic accuracy of CRP were 85.11%, 43.40%, 57.14%, 76.67% and 63% respectively. Conclusion: CRP estimation is a rapid test with good sensitivity and aids in rapid diagnosis of neonatal septicaemia.